From model to methodology: developing an interdisciplinary methodology for exploring the learning–teaching nexus. Issue 3 (27th May 2017) - Knewstubb, Bernadette; Nicholas, Howard
ABSTRACT: Numerous higher education researchers have studied the ways in which students' or academics' beliefs and conceptions affect their educational experiences and outcomes. However, studying the learning–teaching relationship has proved challenging, requiring researchers to simultaneously address both the invisible internal world(s) of the student and teacher, and the observable communicative world they inhabit. This paper describes the development of a methodological approach for exploring the learning–teaching relationship based on an interdisciplinary conceptual model – The Learning–Teaching Nexus (LTN). We describe the ways in which disciplinary perspectives within the model were translated into methodological processes, enabling us to study teaching and learning as both individual experiences and a shared communicative relationship. The paper aims to provide researchers with a staged approach for studying learning and teaching together, and to illustrate how interdisciplinary perspectives can be translated into staged but integrated methodological processes in order to address complex educational questions.